The ELC An Early Childhood Learning Community at Work - Bridge, Heather; Melita, Lorraine; Roiger, Patricia; Open Textbook Library (Open Textbook Library, 2020)
The ELC professional development model was designed to improve the quality of teacher candidates' Practicum field placements and align teaching in field placements with Learning Standards used in the teacher education program. Teams of four educators from varied settings worked in a Practicum placement setting for one semester to improve their teaching and align it with Learning Standards. An action research approach improved teaching challenges teams faced. Research articles were read to improve teams' teaching challenges by implementing one agreed strategy. Teams video-recorded, assessed, and reflected on the impact of the strategy on their teaching, on teacher candidates' learning and on children's learning. This text compiles six case studies from this model to illustrate how teaching challenges were improved. Appropriate for practiced educators as well as educators in training, this text provides a real world look into applying Learning Standards in early childhood classrooms.
Part I: Setting up the Early Learning Community (ELC) -- 1. Building Blocks for the ELC -- Part II: Case Studies2. Improving Children's Socio-Dramatic Play -- 3. Developing a Science Area -- 4. Improving Opportunities for Physical Play -- 5. Improving Play at the Sensory Table -- 6. Boys' Capacity to Express Emotions -- 7. Improving Differentiation during Morning Meetings -- Part III: Reflections -- 8. Participants' Responses to the ELC -- 9. Conclusion -- Appendix A: Educators' Questionnaire -- Appendix B: Teacher Candidates' Questionnaire
In English.
Description based on online resource
Keywords: Early Childhood -- Textbooks